Implementasi Manajemen Backup Data Berbasis Strategi Backup Rule 3-2-1 - ilpan rusilpan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
This study concern the implementation of data backup management based on 3-2-1 backup stategy using NAS synolgy, which authenticates user access to the server using LDAP (Lightwight Directory Access Protocol) to share data centers per departmental groups. This backup management implementation is implemented at PT Leoco Indonesia where the previous backup system still uses an external 1 tera departmental hard drive and there is no file sharing, this is less effective because it often unplugs the usb hard drive and is prone to damage, the hard drive is often unreadable and data cannot be accessed. The main data on the computer was not spared from damage such as bad sectors hard disk, damaged operating system, ransomware virus attacks which resulted in disrupted work operations hampering business performance. Work data cannot be recovered quickly because there are no other backups. Moreover, data affected by the data ransomware virus cannot be repaired at all. Therefore, data backup management based on the 3-2-1 strategy is needed, to back up layered data backups. and sharing data centers using LDAP authentication, the results of this research are expected to minimize data loss, because data backups have been stored in 3 copies on 2 different types of storage media and there is 1 offsite copy, operating system backup, faster data restoration, data sharing center is running smoothly.